Validity of engagement instrument during online learning in mathematics education - Hidayat, Riyan; Imami, Muh Khairul Wajedi; Liu, Sibo; Qudratuddarsi, Hilman; Mohd Saad, Mohd Rashid (Jambi University, 2024)
The purpose of the current study was to assess the validity of the engagement instrument during online learning in mathematics education. This study used a survey research design as its approach. The participants of the current research were 203 Generation Z students in West Nusa Tenggara Barat, Indonesia. Convenience sampling techniques were used to assess who had completed the online survey. Three procedures were used to analyse the data in this research: exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and Rasch analysis. EFA revealed that online engagement instrument had two sub-components; behavioural engagement and emotional engagement. At the same time, the CFA results showed that the model fit indices established the first-and second-order model's two-factor structure. Finally, the results of the showed that the online engagement instrument’s item and person reliability were good. The findings indicate that there is a potential for enhancement even though the Rasch analysis largely supported the results of EFA and CFA. The current research’s novelty is that it provides a valid and reliable instrument to assess student`s engagement during online learning in a mathematical education context. The use of the current instrument can ensure the accuracy, reliability, and credibility of research related to student engagement during online learning in mathematics education.